IMPLIKASI NILAI MASLAHAT TERHADAP PEMBERDAYAAN TANAH TERLANTAR (IHYA’UL- MAWAT) DI KOTA PALEMBANG - Ayu Ritawati, Raden; Erika Septiana, Raden Ayu; Nurhayat, Muhammad Arpah (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Land should be empowered by being managed and cultivated properly to obtain the greatest possible benefit, in accordance with the provisions of the Basic Agrarian Law and Islamic law. Because neglecting land for any reason is not justified by law, and both Islamic law and the Basic Agrarian Law have clearly mentioned this and even given the state the right to take firm action against applicable violations. This research was conducted to determine the extent of the determination and control of abandoned land that has been carried out in the city of Palembang. As well as its relation to the level of optimization of land management and utilization to obtain economic use value so that what is referred to as adh-dharurat al-khams will be preserved in the form of preserving its assets (hifdz al-mâl) based on the level of importance in accordance with maqasyid as-syariah. In this study, an inductive approach is used where the method used is a qualitative descriptive method, through the theory of maslahat hajiyyat in accordance with the actual description of the research object. The findings obtained in this study are that almost all abandoned land in the city of Palembang has not been fully utilized to meet the economic needs of the local people. In addition, the solution to the problem, secondarily (hajiyyat) the land must be immediately taken over by the government and properly utilized for the fulfillment of the relocation needs of the local community, who are mostly landless and income-poor, and need adequate and representative educational and health facilities. Where the utilization of abandoned land is allocated to overcome the problem of the stability of the distribution of population density that is no longer in line with the area.